Blood cell DNA methylation biomarkers in preclinical malignant pleural mesothelioma: The EPIC prospective cohort. Issue 4 (5th November 2022) - Allione, Alessandra; Viberti, Clara; Cotellessa, Ilaria; Catalano, Chiara; Casalone, Elisabetta; Cugliari, Giovanni; Russo, Alessia; Guarrera, Simonetta; Mirabelli, Dario; Sacerdote, Carlotta; Gentile, Marco; Eichelmann, Fabian; et al.
Abstract: Malignant pleural mesothelioma (MPM) is a rare and aggressive cancer mainly caused by asbestos exposure. Specific and sensitive noninvasive biomarkers may facilitate and enhance screening programs for the early detection of cancer. We investigated DNA methylation (DNAm) profiles in MPM prediagnostic blood samples in a case‐control study nested in the European Prospective Investigation into Cancer and nutrition (EPIC) cohort, aiming to characterise DNAm biomarkers associated with MPM. From the EPIC cohort, we included samples from 135 participants who developed MPM during 20 years of follow‐up and from 135 matched, cancer‐free, controls. For the discovery phase we selected EPIC participants who developed MPM within 5 years from enrolment (n = 36) with matched controls. We identified nine differentially methylated CpGs, selected by 10‐fold cross‐validation and correlation analyses: cg25755428 ( MRI1 ), cg20389709 ( KLF11 ), cg23870316, cg13862711 ( LHX6 ), cg06417478 ( HOOK2 ), cg00667948, cg01879420 ( AMD1 ), cg25317025 ( RPL17 ) and cg06205333 ( RAP1A ). Receiver operating characteristic (ROC) analysis showed that the model including baseline characteristics (age, sex and PC1wbc) along with the nine MPM‐related CpGs has a better predictive value for MPM occurrence than the baseline model alone, maintaining some performance also at more than 5 years before diagnosis (area under the curve [AUC] < 5 years = 0.89; AUC 5‐10 years = 0.80; AUC >10 years = 0.75; baseline AUC range = 0.63‐0.67). DNAm changes as noninvasive biomarkers in prediagnostic blood samples of MPM cases were investigated for the first time. Their application can improve the identification of asbestos‐exposed individuals at higher MPM risk to possibly adopt more intensive monitoring for early disease identification. Abstract : What's new? Malignant pleural mesothelioma (MPM), though rare, is an aggressive cancer chiefly caused by exposure to asbestos. Here, the authors describe a distinctive DNA methylation profile that can help clinicians identify people who are at higher risk of developing MPM. Using samples from 135 individuals who developed MPM and 135 cancer‐free controls, they identified nine sites that had methylation differences between the cancer cases and the controls. This biomarker profile could help screen asbestos‐exposed individuals for MPM and improve early detection.